Diversidade e taxonomia de leveduras isoladas de flores deheliconia psittacorum - Anne Caroline Barbosa (2010)
This study aimed to characterize the yeast community colonizingHeliconia psittacorum (Heliconiaceae) flowers. These flowers were collected near Formiga waterfall, located at the Parque Estadual do Jalapão (state of Tocantins), one of the largest Cerrado reserves in Brazil. Twenty-five flowers of H. psittacorum were collected and 229 yeast isolates were obteinded. These isolates were grouped according to physiological and molecular profile. One isolate from each group was subjected to gene sequencing of the D1/D2 region of rRNA gene. The yeasts were identified as belonging to 20 species, nine ascomycetes species and eleven basidiomycetes. The genus Candida was themost frequent, with 50.64% of total isolates and Candida flosculorum was the specie with the largest number of isolates. This specie seems to be closely related to flowers of Heliconia, as has already been isolated in studies with two other species of this plant genus. Four new species of yeasts were found. Candida sp. belongs to Wickerhamiella clade, being phylogenetically close to C. drosophilae and C. jalaponensis. Candida sp. 2 is a basal species in Metchnikowia clade and is phylogenetically close to C. saopaulonensis. Candida sp. 3 is phylogenetically close to C. asparagi and forms a clade together with C. fructus. Candida sp. 4 belongs to Wickerhamomyces clade and is phylogenetically close to Wickerhamomyces pijperi. Two other species, Cryptococcus sp. (Sequence of the D1/D2 and ITS regions of rRNA identical strain CBS 8369, in Genbank access number AF444705) and "Candidanymphaea" (sequence of the D1/D2 and ITS regions of rRNA identical 05-7 llinhagem-186T, GenBank access number FJ537069) have been isolated from other plants, but have not been described yet. The yeast community isolated from H. psittacorum flowers presents a comprehensive physiological profile, with the assimilation of a wide variety of carbon sources and with the predominance of osmotolerant species, which may be related to the high concentration of sugars in the nectaries. Many species of yeast community use nitrate and nitrite as sole nitrogen source and few are able to ferment glucose and grow at 37°C. The yeast community associated wi th H. psittacorum showedhigh diversity index, with a very similar value to that found for the yeastcommunity of H. velloziana flowers from Mata Atlântica fragments. This study shows that flowers of Cerrado biome can be a rich source of new yeast species. More studies are needed to better characterize the communities colonizing these ephemeral habitats.